Hypothyroidism in pregnancy - a review - Gadomska, Anna; Kurek, Justyna; Gorzyński, Rafał; Garstka, Michał; Dominik, Hanna; Czudy, Zuzanna; Pawęska, Wojciech; Molczyk-Sieńczak, Justyna; Radwański, Jan; Polatowska, Marika (Journal of Education, Health and Sport, 2023)
Introduction: Thyroid diseases, right after diabetes, are the most common endocrine disorder in pregnant women. Hypothyroidism occurs most frequently among all of the thyroid dysfunctions. Thyroid hormones are essential for the proper course of pregnancy and correct fetal development. Even a mild deficiency carries the risk of complications for both mother and child. It is therefore important to make a swift diagnosis, implement appropriate substitution treatment and monitor the course of the disease throughout pregnancy and in the postpartum period. Purpose of the work: The article reviews the current state of knowledge regarding maternal hypothyroidism in pregnancy. The aim of the review is to highlight the prevalence of the disease, stress the associated adverse outcomes and present the recommended management. Materials and methods: A literature research on PubMed, Cochrane Library and Google Scholar databases was done up to May 2023 with restriction to English and Polish language articles regarding hypothyroidism and pregnancy. Summary: It is extremely important to perform TSH screening tests in women planning pregnancy and during the first obstetric visit. Due to the prevalence of thyroid disorders in society, it is necessary to educate both patients and physicians. An uncomplicated diagnosis process, low cost of screening tests and available treatment methods are able to prevent the often tragic consequences of maternal hypothyroidism.